Anti-Inflammatory Effects of (9Z,11E)-13-Oxooctadeca-9,11-dienoic Acid (13-KODE) Derived from Salicornia herbacea L. on Lipopolysaccharide-Stimulated Murine Macrophage via NF-kB and MAPK Inhibition and Nrf2/HO-1 Signaling Activation - Yu-Chan Ko; Hack Sun Choi; Su-Lim Kim; Bong-Sik Yun; Dong-Sun Lee (Antioxidants, 2022)
Glasswort (Salicornia herbacea L.) is a halophyte that exhibits antioxidant and antidiabetic effects. Only a few studies have been conducted on its antioxidant effects. Here, we isolated an antioxidant using an activity-based purification method, and the resulting compound was identified as (9Z,11E)-13-Oxooctadeca-9,11-dienoic acid (13-KODE). We investigated its ability to suppress inflammatory responses and the molecular mechanisms underlying these abilities using lipopolysaccharide-stimulated RAW 264.7 macrophage cells. We studied the anti-inflammatory effects of 13-KODE derived from S. herbacea L on RAW 264.7 macrophages. 13-KODE inhibited lipopolysaccharide (LPS)-induced nitric oxide (NO) production by suppressing inducible NO synthase and suppressed LPS-induced tumor necrosis factor and interleukin-1β expression in RAW 264.7 macrophages. LPS-mediated nuclear localization of NF-κB and mitogen-activated protein kinase activation were inhibited by 13-KODE. 13-KODE significantly reduced LPS-induced production of reactive oxygen species and increased the expression of nuclear factor erythroid-2 like 2 (Nfe2I2) and heme oxygenase 1. Overall, our results indicate that 13-KODE may have potential for treating inflammation.